Susceptibility-Related Factor and Biomarkers of Dietary Supplement Polygonum multiflorum-Induced Liver Injury in Rats - Tu, Can; He, Qin; Li, Chun-Yu; Niu, Ming; Han, Zi-Xin; Ge, Fei-Lin; Zhou, Yuan-Yuan; Zhang, Le; Wang, Xiao-Hui; Zhu, Jing-Xiao; Li, Rui-Sheng; Song, Hai-Bo; et al. (Frontiers in Pharmacology, 2019)
Polygonum multiflorum(PM), a well-known and commonly-used Traditional Chinese Medicine and herbal dietary supplement(HDS) for nourishing the kidney and liver, etc. has aroused wide concern for its reported potential hepatotoxicity. Previous clinical cases and experimental studies have suggested that mild immune stress (MIS) may be one of the susceptibility-related factors of idiosyncratic drug-induced liver injury (IDILI) caused by PM. In this paper, we found that the same dose of PM caused abnormal liver biochemical indicators and liver tissue damage in MIS model rats, while it did not result in liver injury in normal rats, further confirming that MIS is a susceptibility factor for PM-IDILI. Plasma chemokine/cytokine profiling indicated that the MIS model group was significantly different from the other groups, showing a significant upregulation of plasma chemokines, while the MIS/PM group showed upregulated expression of chemokines or pro-inflammatory cytokines. Liver histopathological examination indicated a small amount of inflammatory cytokine infiltration in the MIS group, but no hepatocyte injury, consistent with the plasma profiles of increased chemokines and unchanged inflammatory cytokines. Notably, metabolomics characterization showed that MIS caused reprogramming of these metabolic pathways (such as phenylalanine and glutamate pathways), which was associated with acute phase reactions and inflammatory responses. These results suggested that MIS may promote an immune response to the initial cellular injury induced by PM in the liver, and MIS-induced upregulation of chemokines and metabolic reprogramming may an important mechanism that mediates the susceptibility to PM-IDILI. Furthermore, via receiver operating characteristic (ROC) curves analysis, we identified 12 plasma cytokines (e.g., IP-10, MCP1 and MIP1α) and 9 metabolomics biomarkers (e.g., L-Phenylalanine, Creatinine and L-glutamine) with differential capabilities (all ROC AUC > 0.9) of identifying susceptibility model animals from normal ones, which might be of referable value for the clinical recognition of PM-IDILI susceptible individuals.